ANALISIS KOMPARATIF KINERJA KEUANGAN JASA PERBANKAN MELALUI PENDEKATAN ECONOMIC VALUE ADDED PADA PT. BURSA EFEK INDONESIA - Andi Wira Hadi Kusuma; Sumatriani Sumatriani (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2022)
The problem was related to financial performance using an economic value added. This research aims to assess financial performance based on Economic Value Added (EVA) at PT. Bank Rakyat Indonesia and PT. Bank Mandiri. The method used in this study is the Economic Value Added (EVA) method. EVA analyzes financial performance by paying attention to operating profit and the company's cost of capital. The type of this research is a quantitative description that provides a description and analysis of the results of the EVA calculation. This research uses financial data obtained from the Indonesia Stock Exchange in the 2016-2020. Based on the results of the study, it can be concluded: 1) financial performance based on EVA at PT. Bank Rakyat Indonesia obtained a positive EVA value in 2016 to 2018, while in 2019-2020 it obtained a negative EVA;2) financial performance based on EVA at PT. Bank Mandiri obtained a negative EVA value in 2016, 2019, and 2020, while in 2017-2018 it obtained a positive EVA.